Abdominal lymphatic malformations in children: case series - Carmine Noviello; Alfonso Papparella; Mirko Bertozzi; Giovanna Riccipetitoni; Ilaria Cascone; Carmine Botta; Giulia Fusi; Veronica Vitali; Mercedes Romano (La Pediatria Medica e Chirurgica)
Lymphatic Malformations (LMs) are benign congenital malformations of the lymphatic system that commonly involve the abdomen in children (mesentery of the small intestine and omentum). The management of these malformations is not unique. 7 children with different ages (range: newborn to 14 years), diagnosis was incidental in some cases, while in others for abdominal pain. All patients underwent abdominal ultrasound and Magnetic Resonance Imaging (MRI). Laparoscopy for diagnosis was useful in 4 cases. Treatment was: conservative in 1 child, laparoscopic excision in 3 patients, laparotomic excision in 3 cases. At follow up we observed recurrence in a case that required integrated treatment and bowel occlusion after excision in 1 case. This benign malformations may not cause any symptoms to patient. The goal of treatment is to maintain organ function, preserve aesthetic integrity and complications control. Management of these patients could be varied: the best approach should be evaluated on the basis of the patient.